Efficacy of Online Tutoring Programs: A Comparative Analysis between the United Kingdom and China - Brown, Emily (International Journal of Online and Distance Learning, 2024)
Purpose: The aim of the study was to investigate the efficacy of online tutoring programs: a comparative analysis between the United Kingdom and China. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: A comparative analysis between the United Kingdom and China highlights differences in the efficacy of online tutoring programs. Chinese students show higher engagement, while UK students report greater satisfaction. These findings emphasize the need for culturally tailored tutoring interventions to optimize outcomes across diverse educational settings. Unique Contribution to Theory, Practice and Policy: Social learning theory, cultural-historical activity theory (CHAT) & technology acceptance model (TAM) may be used to anchor future studies on the efficacy of online tutoring programs: a comparative analysis between the United Kingdom and China. Online tutoring programs should prioritize the development of culturally sensitive pedagogical strategies and instructional materials. Policymakers should promote cross-cultural collaboration and exchange in the development and implementation of online tutoring programs.